Isolation, Synthesis, and Fungicidal Activity of Isopropyl (3-methyl-1-oxo-1-((1-((4-(prop-2-yn-1-yloxy)phenyl)thio)propan-2-yl)amino)butan-2-yl)carbamate Diastereomers against Phytophthora capsici. (5th August 2022) - Tian, Lei; Gao, Yang; Peng, Xing-Jie; Zhang, Cheng; Zhao, Wei-Guang; Liu, Xing-Hai
Abstract : Two isopropyl (3-methyl-1-oxo-1-((1-((4-(prop-2-yn-1-yloxy)phenyl)thio)propan-2-yl)amino)butan-2-yl)carbamate diastereomers were isolated. Fungicidal activities indicated that the isolated four chiral compounds possessed excellent activity against P. capsici with the EC50 value of 4a (1.30  μ g/mL), 4b (0.078  μ g/mL), 4c (1.85  μ g/mL), and 4d (44.4  μ g/mL). Among them, compound 4b exhibited remarkably high activities against Phytophthora capsici, which is better than that of positive control dimethomorph. Its R and S isomers showed that chiral influences the activity against P. capsici .